Characteristics and risk profile of the over fifty adult congenital heart surgical population, a retrospective cohort - Bieze, Matthanja; Poole, Oliver; Delfani, Arshia; Heggie, Jane; Salvatori, Marcus (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThe surgical and medical management of aging patients with adult congenital heart disease (ACHD) continues to innovate to meet the evolving needs of this unique patient population, leading to improved life expectancy and quality of life. However, the ACHD population is characterized by high morbidity and mortality. With this study, we aim to describe patient characteristics and surgical outcomes for the over fifty ACHD cardiac surgical cohort, focusing on risk factors for mortality and major complications.MethodsThis was a retrospective cohort study including ACHD patients undergoing surgical repair from January 2004 to March 2023. Primary outcome was the composite of severe postoperative complications and secondary outcomes were 1-year mortality, ICU stay and hospital length of stay. Descriptive statistics,univariable and multivariable logistic regression models were used.ResultsIn the study period, 1381 patients with ACHD underwent cardiac surgery, of which 292 (20.5%) were over 50 years. In the overall group, the most common primary surgery was pulmonary valve replacement in 411 (29.8%), in the over 50 group this was ASD and VSD repairs in 102 (34.9%). The composite of major postoperative complications was different between the overall group and the over 50 years group (10.7% vs. 13.7%; P = 0.049), which in the over 50 group was associated with CPB time (180 min vs. 104 min, OR 1.01; 95%CI 1.00–1.03), and preoperative creatinine levels (84 vs. 77, OR 1.01; 95%CI 1.00–1.03). No difference was seen in 1-year mortality (P = 0.415).ConclusionWith careful patient selection and preoperative optimization, surgical risks remain low, even in aging ACHD patients. Although overall mortality rates are low, postoperative complications increase, and patients over 50 with DM, renal failure, long pump runs or postoperative stroke are at highest risk.